Accountants and the Cloud – Involving the Professionals - Dragoș Mangiuc (Journal of Accounting and Management Information Systems (JAMIS), 2017)
As the cloud-based technologies gain more customers each day, the need for understanding the "economics of cloud" arises, together with the need for strategic measurement of different cloud or non-cloud-based infrastructure options. In such context, the option for the cloud technologies cannot be the duty of the IT department only, as the economic drivers are at least as important as the technological ones. Economic measurement of the future cloud computing implementations is required for at least two reasons. First, all types of implementations are investment projects and, by consequence, need to be fully justified before being chosen or rejected. Second, once a cloud strategy is adopted and an infrastructure is implemented, the implementation must be continually monitored, so the organization can be sure that it continues to deliver an optimal return on investment. Gaining maximal return on the implementation of a cloud computing strategy is predicated on the ability to understand the economic metrics. Therefore, the accounting professional can no longer be a simple observer in the process of cloud migration and cloud adoption, but a central piece and a "voice of reason" standing between the typical enthusiasm of the IT department and the typical skepticism of the management.
Keywords: L86; 650; Cloud computing economics; accounting profession; CAPEX; OPEX; ROI; TCO